A study of role of brachytherapy IR192 in treatment of eyelid tumors - Jitendra Manghani; Khalid Khan (International Journal of Medical Research and Review, 2016)
Background: In eye lid cancers, there is a significant risk for tissue damage to nearby vital ocular structures and even of blindness. The skin around the eyelid is thin and contains little subcutaneous tissue and anatomic connections to the underlying bone in the region facilitate rapid local tumor spread into the nasal and orbital cavities.Objective: The aim of this study was to evaluate the response of high dose rate interstitial brachytherapy in carcinoma eye lid.Methodology: From January 2011 to December 2012, 25 diagnosed cases of carcinoma eye lid were reported in our department. All cases were staged clinically according to the TNM staging system. All patients were treated with high dose rate interstitial implant and analyzed for presence of residual disease, local recurrence, distant metastasis, radiation reaction and disease free survival.Result: Total 25 cases were examined, 12 were males while 13 were females. Most of the tumors were involving the lower lid. Squamous cell carcinoma out numbered the basal cell carcinoma. Basal cell carcinoma group of 11 cases, 91% showed complete regression at 6 months while Squamous cell carcinoma group of 14 cases, 93% showed total regression.Conclusion: High dose rate interstitial brachytherapy with Iridium 192 is appropriate for the treatment of early staged squamous cell carcinoma of eye lid.